Behavioral Responses of Zebrafish to Selected Chemical Constituents of the Skin - Schadegg, Philip; Koenigsburg, Cynthia; Seravalli, Claudia (My University, 2015)
The purpose of this study was to develop a behavioral assay to characterize the "alarm response" in Zebrafish and to describe their behavior following exposure to chondroitin, and chemical components of cultured skin cells. In developing a behavioral assay, our objective was to evaluate behavioral responses to the different treatments.
Color poster with text, graphs, and photographs.
Keywords: Ostariophysian fish; Danis rerio; Zebrafish; Posters